A body-oriented approach when the body is problematic: Psychomotor physiotherapy as an approach in the treatment of patients with eating disorders: An interview study - Karine Børsum; Målfrid Råheim (Fysioterapeuten, 2017)
Background: Research on the treatment of patients with eating disorders is comprehensive, but little exists on treatments that are based on bodily experience. This is despite the fact that this is an illness that is closely associated with the body. The aim of this study was to look at the contribution of psychomotor physiotherapy in the treatment of patients with an eating disorder, seen from the therapist perspective. Method: Semi-structured interviews with therapists in the same team were carried out at a special unit for eating disorders. Psychomotor physiotherapist, psychologist, psychiatrist and specialist nurse. The analysis was conducted using systematic text condensation. Findings: The findings consist of two main topics: I. The contribution of the psychomotor physiotherapist to the treatment: ‘the body expert’, with the following subtopics: Working directly on the body: About going straight to the core; and Dissemination of knowledge about the body and training. II. The treatment team: Interdisciplinary cooperation in practice, with the following subtopics: About treatment teams, treatment meetings and treatment content; and Cooperation based on common understanding and equality. Conclusion: Psychomotor physiotherapy contributed something that is essential to, different from and complementary to the other approaches in the interdisciplinary team in the treatment of patients with eating disorders. The body-oriented approach was associated with ‘getting straight to the core of the matter’ and was therefore considered important.